Pengaruh Ukuran Perusahaan dan Diversifikasi Terhadap Financial Distress (Studi Empiris pada Perusahaan Manufaktur Subsektor Tekstil dan Garment yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Kristianti, Deviliana; Khairudin (Jurnal EMT KITA, 2024)
The aim of this research is to show empirically how company size and diversification affect Financial Distress. Company size and diversity are the two independent factors studied. Secondary data used in this research comes from the 2019–2021 financial reports of companies listed on the IDX. A total of 10 companies were used in the purposive sampling approach. Logistic regression analysis is the method used for data analysis. The results show that company size has a negative and significant impact if Financial Distress occurs, but diversity does not have a significant impact.